Differential expression of Triggering Receptor Expressed on Myeloid cells 2 (Trem2) in tissue eosinophils. Issue 4 (6th January 2021) - Sek, Albert C.; Percopo, Caroline M.; Boddapati, Arun K.; Ma, Michelle; Geslewitz, Wendy E.; Krumholz, Julia O.; Lack, Justin B.; Rosenberg, Helene F.
Abstract: No longer regarded simply as end‐stage cytotoxic effectors, eosinophils are now recognized as complex cells with unique phenotypes that develop in response stimuli in the local microenvironment. In our previous study, we documented eosinophil infiltration in damaged muscle characteristic of dystrophin‐deficient (mdx) mice that model Duchenne muscular dystrophy. Specifically, we found that eosinophils did not promote the generation of muscle lesions, as these persisted in eosinophil‐deficient mdx.PHIL mice. To obtain additional insight into these findings, we performed RNA sequencing of eosinophils isolated from muscle tissue of mdx, IL5tg, and mdx. IL5tg mice. We observed profound up‐regulation of classical effector proteins (major basic protein‐1, eosinophil peroxidase, and eosinophil‐associated ribonucleases) in eosinophils isolated from lesion‐free muscle from IL5tg mice. By contrast, we observed significant up‐regulation of tissue remodeling genes, including proteases, extracellular matrix components, collagen, and skeletal muscle precursors, as well as the immunomodulatory receptor, Trem2, in eosinophils isolated from skeletal muscle tissue from the dystrophin‐deficient mdx mice. Although the anti‐inflammatory properties of Trem2 have been described in the monocyte/macrophage lineage, no previous studies have documented its expression in eosinophils. We found that Trem2 was critical for full growth and differentiation of bone marrow‐derived eosinophil cultures and full expression of TLR4. Immunoreactive Trem2 was also detected on human peripheral blood eosinophils at levels that correlated with donor body mass index and total leukocyte count. Taken together, our findings provide important insight into the immunomodulatory and remodeling capacity of mouse eosinophils and the flexibility of their gene expression profiles in vivo. Graphical Abstract: The flexibility of eosinophil gene expression profiles in vivo supports the LIAR hypothesis of eosinophil function.